Comparison of JAWS and NVDA as Assistive Technology for College Students with Special Needs at Universitas Negeri Surabaya - Ersanty, Dhany; Wibisono, Sindu Sony; Niratama, Fairus; Sasongko, Tri Budi (JPI (Jurnal Pendidikan Inklusi), 2019)
Today Assistive technology is an important point that cannot be released from MBK (Students with Special Needs) as supporting advice in the lecture. This is also based on Article 5 paragraph (2) letter g Permendikbud number 46 of 2014; where one of them mentioned that universities should have a talking book . for Students with Special Needs, application is a support in daily activities, especially in the lecture process to facilitate these students in processing the information submitted in the discussion process. Some applications used by Students with Special Needs Especially blind people are JAWS and NVDA. JAWS itself is Job Access With Speech which is a screen reader application or (screen reader) is a software for help blind people operate a computer or PC. This study uses a qualitative approach with a subject of 5 people. Technique data collection through interviews and observations. from the results of the study of 5 subjects the majority use a combination of the two applications on the device. Results found analysis that the two applications do not affect learning outcomes and do not exist more effectively, both applications support simultaneously when used both offline and online.